Implementasi Sistem Informasi Audisi Modelling Pada Kegiatan Audisi FKBN TMI JATIM SEKARISIDENAN Kediri 2023 - Erna Daniati; Aidina Ristyawan; Rina Firliana; Anita Sari Wardani; Muhammad Najibulloh Muzaki (Jurnal TUNAS, 2023)
Modelling Audition Information System is a system used to manage the process of auditioning or selecting potential models in the modelling industry. This system helps collect, store, manage, and process information related to auditions and model selection to make the process more efficient and organized. The information system is used for participant registration and conducting judging. This Information System is a form of community service implementation for the FKBN TMI Jatim Kediri Subdistrict Audition in 2023. The Forum Kader Bela Negara (FKBN) was attended by thousands of spectators and visitors in Ketos on Sunday, July 9, 2023, in conjunction with National Children's Day and in anticipation of the 78th Indonesian Independence Day. FKBN Kediri Raya provides a great opportunity to help improve the upgrading of SMEs in makeup, fashion design, SMEs fashion model training, and style. The formation of confident character and healthy social interactions creates intelligent, observant, and militant defense souls. With the presence of the modelling audition information system, the audition and model selection process becomes more structured, transparent, and efficient. This system helps reduce human errors, save time, and facilitate coordination among all parties involved in the modelling audition.